Strategi Komunikasi Orangtua dan Anak Generasi Z dalam Merespons Fenomena ‘Marriage Is Scary’: Analisis Konten pada Platform Tiktok - Fithri Az-Zahra; Lies Utami Efni Safitri (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
The growing "Marriage Is Scary" phenomenon on TikTok reflects a shift in Generation Z's perspective on the institution of marriage within the context of digital culture. This trend highlights narratives of fear of long-term commitment, domestic conflict, economic pressure, and gender role inequality. This study aims to analyze the representation of communication strategies between Generation Z parents and children to uncover this phenomenon on TikTok and understand the dynamics of intergenerational communication that are formed. This research shows that social media plays a role in shaping the construction of the meaning of marriage through the fragmentation of negative narratives that are then internalized in Generation Z's perceptions. However, this influence is not deterministic. Family communication has been shown to be a dominant factor in shaping children's final attitudes toward marriage. Parents employ four main communication strategies: normative-religious, dialogical, role-modeling, and adapting to digital culture. Meanwhile, children's responses demonstrate the dynamics between the influence of social media and family experiences. This study concludes that the "Marriage Is Scary" phenomenon is not a rejection of marriage, but rather a reflection of the transformation in how the younger generation interprets commitment in a digital society. Healthy and open family communication is key to bridging intergenerational perspectives